Water Quality Analyses: Evidence from River Gashua and Some Selected Groundwater Sources in Gashua, Nigeria - Amoo Afeez Oladeji; Adeleye Adeniyi Olarewaju; Bate Garba Barde; Asaju Catherine Iyabo; Isiaq Saheed Mohammed; Ilyasu Yusuf Adamu (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
The interface between surface water and groundwater is becoming more complex owing to the effects of climate change and anthropogenic activities these days. In this study, the physicochemical; pH, color, electrical conductivity, total dissolved solids, and turbidity while bacteriological parameters; total and fecal coliform of water samples from River Gashua and its surrounding wells in Gashua local government area of Yobe State were assessed. All the physicochemical parameters were analyzed using water quality standards. Fecal and total coliforms were assayed using the filter membrane technique. The results obtained from the physicochemical parameters of Boreholes (BH1, BH2, and BH3) and hand pump wells (HPW1, HPW2, and HPW3) are within the World Health Organization (WHO) standards. However, the river (R) water sample was found to have a high concentration in total dissolved solids, turbidity, and color than permissible standards. Bacteriological analysis revealed the presence of total and fecal coliform in the water samples; R, BH2, BH3, HPW1, HPW2, and HPW3. The findings indicate that there is a need to protect the quality of the river system. Therefore, it is recommended that government and other stakeholders should take appropriate and corrective actions to avert the continuous discharge of waste products into the river. Again, Yobe State Ministry of Environment should ensure that all public boreholes are routinely subjected to appropriate water assays to ascertain their suitability for human consumption.